Knowledge Of Fast Food With The Incidence Of Obesity In Adolescents At Smp Negeri 5 Denpasar - Nurul Faidah; I Putu Gede Sanjaya; M. Adreng Pamungkas (Universitas Kadiri, 2024)
Teenagers today are not fully able to control a good diet, because, in this day and age, most teenagers choose more instant food, for example, fast food. The impact that results from consuming fast food excessively is obesity. The purpose of this study is to determine the relationship between the level of knowledge about fast food and the incidence of obesity in adolescents at SMP Negeri 5 Denpasar. This study is a quantitative research using a correlational descriptive design with a cross-sectional approach model. The sample in this study namely the students of SMP Negeri 5 Denpasar who amounted to 281 respondents which was determined using the Slovin formula. The sampling technique uses simple random sampling with a proportional approach. The research instruments used are questionnaires as well as analog and microtome scales. This study used univariate and bivariate (rank spearmen) data analysis. The results of this study showed that the level of adolescent knowledge about fast food, the majority of whom had insufficient knowledge, amounted to 103 respondents (36.7%) and the incidence of obesity amounted to 86 respondents (30.6%). The results of the observation of the variable relationship between the level of knowledge about fast food and the incidence of obesity obtained a p-value value = 0.000 or p-value <0.05 there is a significant relationship between the level of knowledge about fast food with the incidence of obesity in adolescents at SMP Negeri 5 Denpasar. Respondents' lack of knowledge about the high frequency of fast food consumption activities can trigger the risk of health problems, one of which is obesity.